Dim Light at Night Impairs Daily Variation of Circulating Immune Cells and Renal Immune Homeostasis - Okuliarova, Monika; Mazgutova, Nikoleta; Majzunova, Miroslava; Rumanova, Valentina Sophia; Zeman, Michal (Frontiers in Immunology, 2021)
Dim light at night (dLAN) has become a pervasive part of the modern world, and growing evidence shows its association with increased health risks. Though this link is attributed to a disturbed circadian clock, the underlying mechanisms that can explain how circadian disruption from dLAN causes negative health effects remain unclear. Here, we exposed rats to a light–dark cycle (12:12 h) with low-intensity light at night ( 2 lx) for 2 and 5 weeks and explored the steady-state pattern of circulating immune cells and renal immune-related markers, which are well controlled by the circadian clock. After 5 weeks, dLAN impaired the daily variation in several types of white blood cells, especially monocytes and T cells. Two-week dLAN caused a reduction in blood monocytes and altered gene expression of macrophage marker Cd68 and monocyte-attracting chemokine Ccl2 in the kidney. Interestingly, dLAN decreased renal 3-nitrotyrosine levels and resulted in up-regulation of the main endogenous antioxidant pathways, indicating a disturbance in the renal redox balance and an activation of compensatory mechanisms. These effects paralleled the altered renal expression of the molecular clock components and increased plasma corticosterone levels. Together, our results show that chronic exposure to dLAN weakened the circadian control of daily variation of circulating immune cells and disturbed renal immune and redox homeostasis. Consequences of this dLAN-disturbed immune balance on the ability of the immune system to cope with other challenges should by clarified in further studies.